An intelligent humidity control system for mushroom growing house by using beam-switching antennas with artificial neural networks - Prapan Leekul; Thunyawat Limpiti; pornpimon Chaisaeng (International Journal of Electrical and Computer Engineering (IJECE), 2023)
An automatic humidity control system for mushroom growing house based on the free-space technique is presented. The novelty of this work is the modified free-space technique by measuring the amplitude only of transmission coefficient |S21| that reflected from mushroom by using beam-switching antenna with artificial neural networks (ANNs) as a humidity sensor to control quantity and time of water misting nozzle. In the proposed system, the antenna is designed to act as the transmitting antenna at the frequency of 2.45 GHz. Its radiation patterns can be switched to 4 directions covering all corners of mushroom growing house. The measured |S21| from each direction are converted to direct current (DC) voltage by a radio frequency (RF) detector; then are trained with ANNs in the humidity range of 60-85%. The optimized ANNs structure consists of 4 input nodes, two layers of 5 hidden nodes, and 3 output nodes. To verify the proposed system, experiments were set up in controlled humidity mushroom growing house at the humidity level of 75-80% for 120 hours. The results showed that there was slightly average standard deviation (S.D.) of humidity level 1.36. Consequently, the performance of sensor system assures that it is able to apply for humidity control in large growing house.